Kajian Kritis Literasi Halal dalam Pariwisata: Penyelenggaraan Biro Perjalanan Berdasarkan Fatwa DSN-MUI No. 108/2016 - bin Lahuri, Setiawan; Purnamasari, Fatimah Wulan (Innovative: Journal Of Social Science Research, 2024)
Halal tourism in Indonesia faces challenges in the implementation of sharia standards in travel agencies, despite its great potential. This study aims to analyse the implementation of DSN-MUI Fatwa No. 108/2016 by travel agencies and identify challenges and opportunities for development. Using a qualitative method with literature study and content analysis, this study examined scientific articles, policy documents, and industry reports. Data analysis was conducted through thematic and comparative content analysis. Results show variations in the understanding and implementation of the fatwa, with technological innovation and stakeholder collaboration as key success factors. Key challenges include service standardisation and improving halal literacy, while opportunities lie in innovative product development and technology integration. The findings underscore the need for a holistic and sustainable approach to face challenges and capitalise on opportunities in halal tourism. Recommendations for policy and practice development in the sector are also suggested to enhance the effectiveness and sustainability of halal tourism in Indonesia. Keyword: halal tourism, travel agency, sharia fatwa, innovation